The Role of Rice’s Price in the Household Consumption in Indonesia - Dian Hafizah; Dedi Budiman Hakim; Harianto Harianto; Rita Nurmalina (Agriekonomika, 2020)
The purpose of the study was to analyze the role of rice’s price in household consumption patterns in Indonesia. The method used was the Quadratic Almost Ideal Demand System (QUAIDS). The data used were obtained from the National Social Economy Survey in 2016. The results show that when the price of rice increases by one percent, the demand for other carbohydrates, eggs-milk-beans, fruits also Cigarette and processed foods will be increase. Meanwhile, in other groups, when the price of rice rises, the demand will go down. Thus, it can be concluded that households still prioritize rice consumption in their daily consumption patterns compared to other commodity groups. Therefore, the government should develop policies that encourage people to consume more diverse food groups.